Film and TV-induced tourism: the East Asian persepctive - Lin, Fang-Yu (2008)
Researchers of film and television-induced tourism have often suggested that destinations showed on the films and television would be likely to attract a massive number of tourists to visit the filmed locations. However, research which has empirically and theoretically documented the link between screen products and tourism is scant. Therefore, the aim of this research attempts to explore how featured locations and tourism are related. This research involved focus group interview and an online-questionnaire-based survey. 6 participants in focus group interview and 225 participants in online questionnaire of five East Asian countries took part in the study. The quantitative analysis of the questionnaires was conducted through descriptive statistics and Pearson's correlation in order to indicate the relationship between these two variables. Results of this study showed a low level of consistence between featured locations and tourism. To conclude, this study may be of importance in explaining the East Asian's perspectives of films and TV to induced tourism, as well as in providing destination marketing organisations with a better understanding of the effects of films and TV miniseries on tourism.